2017
DOI: 10.17511/ijmrr.2017.i10.02
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional study of differences in phenomenology of acute psychosis with or without cannabis

Abstract: Background: Therehas been plethora of research regarding cannabis use disorder but very few studies reported demographic and phenomenological differences of acute psychosis with cannabis use to those of acute psychosis without cannabis use. This study attempted to evaluate the demographic and phenomenology differences between two groups of patients presenting with acute psychosis with cannabis use and acute psychosis without cannabis use. Material & Method: Two group of patients recruited for study were 'Cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Pal VS et al in this issue found that Acute psychosis with cannabis is characterized by primarily polymorphic clinical picture with predominance of positive and mood symptoms both in clear and disturbed sensorium. Acute psychosis without cannabis is characterized by mixed positive and negative symptoms [12].…”
mentioning
confidence: 99%
“…Pal VS et al in this issue found that Acute psychosis with cannabis is characterized by primarily polymorphic clinical picture with predominance of positive and mood symptoms both in clear and disturbed sensorium. Acute psychosis without cannabis is characterized by mixed positive and negative symptoms [12].…”
mentioning
confidence: 99%